Uganda - Public Expenditure Review : Strengthening the Impact of the Roads Budget - World Bank (World Bank, 2012)
Uganda needs to focus on improving the effectiveness of its roads investment strategy for rural Uganda and improving the manner in it procures and implements roads contracts at the national level. In recent years the Government of Uganda has shifted the priorities in its national development strategy as there was accumulating evidence that infrastructure deficiencies had become a binding constraint to economic growth and poverty reduction. Consequently the Government of Uganda increased in particular the budget allocation for the road sector substantially as a means to tackle this constraint to growth and poverty reduction: i) by investing in rural roads it aims to facilitate market access for farmers, which will allow them to increase their earnings capacity; and ii) by improving the national roads network, transport cost will be reduced, competitiveness enhanced and additional income generated. However, to ensure the highest economic return for its investment, it is advised to rebalance the way allocations are set for rural roads and to increase absorptive capacity to efficiently utilize the augmented budgetary resources for the national roads sector.